Immediate demand reduction in simultaneous ascending bid auctions - Frank Riedel; Elmar Wolfstetter (Center for Economic Studies and ifo Institute (CESifo), 2004)
The present note analyzes the Simultaneous Ascending Bid Auction with arbitrarily many bidders with decreasing marginal valuations under complete information. We show that the game is solvable by iterated elimination of weakly dominated strategies if the efficient allocation assigns at least one unit to every player and if bid increments are sufficiently small. In that unique equilibrium, bidders immediately reduce their demand to the efficient allocation, and the auction ends in the first round of bidding.
Keywords: D45; D44; 330; Simultaneous Ascending Auction; weak dominance; multi-unit auctions; game theory; Auktionstheorie; Vollkommene Information; Theorie